The effectiveness of infiltration box in reducing surface runoff / Noorashiekin Khalid - Khalid, Noorashiekin (2014)
The laboratory scale infiltration box was introduced to temporarily store stormwater, act as medium to determine the most suitable depth of material compositions and determine the optimum of retention time. The infiltration trench is introduced as structural protection measure, reducing the surface runoff and thus to imply solving the floods problem in certain area. The main objectives of this study are to study the effect of variation depth and different material compositions to the infiltration rate, determine the water retention time for different material compositions and determine the effectiveness of infiltration box in reducing surface runoff The objectives were achieved by constructing three infiltration boxes which conducted in laboratory scale of plot 0.4m (length) x 0.4m (width) x 0.6m (depth) container. Two types of soil used were fine sand and medium gravel separated with wire mesh. A number of data of retention time, volume contribute to saturate the material compositions and water quality parameters were analysed. World Health Organization (WHO) and Malaysia Standard were used to evaluate the water quality. The variation depth and different material compositions were generated an impact to the infiltration rate and produced different water quality. The infiltration box with combination of 0.1m depth of fine sand and 0.3m depth of medium gravel was found to be the best result in retain the water in optimum time which recorded time and saturated volume is 489s and 28.5£ respectively. 384 laboratory scale infiltration boxes or suggested to 1 Im (length) x Im (width) x Im (depth) size of infiltration trench provide per houses in Langat catchment area with capability to hold water for 2.2 days represent the effectiveness of the infiltration box in reducing surface runoff